Volunteered Geographic Information (VGI) in Spatial Data Infrastructure (SDI) Continuum - Shahi, Kamal (2023)
Shahi, K. (2023). Volunteered Geographic Information (VGI) in Spatial Data Infrastructure (SDI) Continuum. EAI Endorsed Transactions on Internet of Things, 9(1), 1-8. [e3]. https://doi.org/10.4108/eetiot.v9i1.2979